Differentiation of peripheral sensory neurons from iPSCs derived from stem cells from human exfoliated deciduous teeth (SHED) - Oliveira, Nathalia C.; Russo, Fabiele B.; Beltrão-Braga, Patricia C. B. (Frontiers in Cell and Developmental Biology, 2023)
Peripheral nervous system (PNS) sensory alterations are present in several pathologies and syndromes. The use of induced Pluripotent Stem Cell (iPSC) technology is an important strategy to produce sensory neurons from patients who are accomplished in terms of sensory symptoms. The iPSC technology relies on manipulating signaling pathways to resemble what occurs in vivo development, and the iPSCs are known to carry a transcriptional memory after reprogramming, which can affect the produced cell. On this date, protocols described for sensory neuron production start using iPSC derived from skin fibroblasts, which have the same ontogenetic origin as the central nervous system (CNS). Since it is already known that the cells somehow resemble their origin even after cell reprogramming, ideally, PNS cells should be produced from cells derived from the neural crest cells. This work aimed to establish a protocol to differentiate sensory neurons derived from stem cells from human exfoliated deciduous teeth (SHED) with the same embryonic origin as PNS. SHED-derived iPSC were produced and submitted to peripheral sensory neuron (PSN) differentiation. Our protocol used the dual-SMAD inhibition method followed by neuronal differentiation, using artificial neurotrophic factors and molecules produced by human keratinocytes. We successfully established the first protocol for differentiating neural crest and PNS cells from SHED-derived iPSC, enabling future studies for PNS pathologies.